Gender and sexual violence among students at a brazilian university Violência de gênero e sexual entre alunos de uma universidade brasileira - Vilma Zotareli; Anibal Faúndes; Maria José Duarte Osis; Graciana Alves Duarte; Maria Helena de Sousa (Instituto Materno Infantil de Pernambuco, 2012)
OBJECTIVES: the prevalence of gender and sexual violence, its association with gender and ethical attitudes and the experience of suffering and perpetration of violence were evaluated among students at a public university in Brazil. METHODS: a cross-sectional study analyzed the answers given by 2430 students to a questionnaire sent by internet. RESULTS: among girls, 56.3% had been subjected to some kind of violence and 9.4% to sexual violence since university admission; 29.9% of men reported having perpetrated some kind of violence, 11.4% gender and 3.3% sexual violence. Multivariate analysis showed that living with parents/relatives was a protective factor for women being subjected to and men perpetrating sexual violence but not for "any type of violence". Lower scores for ethical attitudes were associated with a greater likelihood of men perpetrating any kind of or gender violence. Student for whom religion was important had a lower risk of being a perpetrator of any type and of sexual violence, but not gender violence. CONCLUSIONS: the findings may be useful for the discussion of this problem and to propose interventions to prevent or minimize the problems of gender and sexual violence on campus. Further studies in other university contexts need to be carried out to increase knowledge and explore possibilities for intervention. OBJETIVOS: avaliar a prevalência de violência de gênero e sexual e sua associação com atitude de gênero e ética e a experiência de sofrer e perpetrar violência, entre alunos de uma universidade pública no Brasil. MÉTODOS: estudo transversal que analisou as respostas de 2430 alunos a um questionário enviado por internet. RESULTADOS: entre as alunas, 56,3% sofreram algum tipo de violência e 9,4% sofreram violência sexual desde seu ingresso na universidade; 29,9% dos homens declararam ter perpetrado algum tipo de violência; 11,4% violência de gênero e 3,3% violência sexual. Análise multivariada apontou que viver com pais/parentes foi um fator que protegeu as mulheres de sofrerem e os homens de perpetrarem violência sexual, mas não "qualquer tipo de violência". Baixa pontuação no escore de atitude em ética esteve associada a alta probabilidade dos homens perpetrarem "qualquer tipo de violência" e violência de gênero. Os alunos que davam importância à religião tiveram risco menor de serem perpetradores de "qualquer tipo de violência" e de violência sexual, mas não de violência de gênero. CONCLUSÕES: os achados podem ser úteis para a discussão desse problema e para propor intervenções para prevenir ou minimizar os problemas de violência de gênero e sexual no campus. Além disso, requerem-se mais pesquisas para ampliar o conhecimento e as possibilidades de intervenção.